SISTEM KLASTER DALAM PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) SIAP MENGAHADAPI TANTANGAN ASEAN FREE TRADE ASSOCIATION DAN MASYARAKAT EKONOMI ASEAN TAHUN 2015 - Abdul Haris (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2014)
The development of management theory developed very rapidly. early management pioneers was Robert Owen (1771-1858) and Charles Babbage (1792-1871), and continues to evolve with various schools and scientists in the field of view of the management of the flow of scientific management , classical to modern management. Therefore, the discussion and understanding of the management of the target, need to know first the development of theories and principles that will provide a